Are immigrants allowed to criticize the government? Ingroup identity, economic threat, and majority group support for immigrant civil liberties in the US, Switzerland, and Turkey - Gandenberger, Mia K.; Buyuker, Beyza E.; Manatschal, Anita; Filindra, Alexandra (Frontiers in Sociology, 2025)
Assaults on immigrants’ civil liberties have been on the rise across Western countries. This study asks whether majority-group natives exhibit less political tolerance (i.e., support for restrictions on civil rights and liberties) toward immigrants who criticize the government compared to citizens, adding thereby a neglected element to the discussion on the conflicted nexus between migration and citizenship. Drawing on social identity theory and theories of economic threat, we find that across three countries (US, Switzerland, and Turkey) immigrant critics are more strongly penalized. However, the size of the penalty is not moderated by ingroup identity salience, but there is evidence in the US that ingroup victimhood—a different measure of ingroup attitudes—does moderate the treatment effect. Moreover, in all three countries, the treatment effect is amplified by economic threat, and in the US and Turkey, but not in Switzerland, we find significant three-way interactions between the treatment, ingroup identity salience, and economic threat, showing that economic threat activates the effect of ingroup salience. Our findings add to the inconclusive existing evidence on the link between identity salience and political intolerance, by showing that only in combination with realistic feelings of threat (economic threat or victimization) will national or white identity amplify political intolerance towards immigrants.